Quantitative Kinematic Assessment of the Sit-to-Stand Transition using an IMU Sensor - Amici, Cinzia; Ragni, Federica; Tiboni, Monica; Pollet, Joel; Buraschi, Riccardo (2021 24th International Conference on Mechatronics Technology (ICMT), 2021)
Objective: The sit-to-stand transition is an important task for the evaluation of physical independence, especially in fragile subjects like elderly patients, to monitor and reduce the risk of falls or damage. This study aims at assessing the kinematic characteristics of the sit-to-stand transition from a quantitative perspective, using a wireless IMU sensor, and describes a set of parameters suitable for evaluating the movement performance in everyday practice. Methods: An acquisition campaign was designed and carried out on 20 healthy subjects and 13 patients to evaluate acceleration and angular velocity generated during a sit-to-stand task. For each subject, at least four acquisitions were performed, to create a final dataset of 173 acquisitions. The values of the proposed parameters were computed, and results were analyzed with descriptive statistics. Results: According to the proposed parameters definitions and the analyzed dataset, acceleration-and angular velocity-related parameters present statistically significant differences between healthy and pathological data samples, unlike total time TT.